High quality liquid crystal displays and smart devices. Volume 2, - Ishihara, Shoichi; Kobayashi, Shunsuke; Ukai, Yasuhiro (IET, 2019)
LCDs are today the most important flat panel display and their development shows no sign of slow-down. This book aims to describe the trends, challenges and potential solutions of this exciting technology to young scientists and engineers working on liquid crystal displays and in its numerous related fields. The book targets not only liquid crystal experts but also newcomers. The extensive list of references and a discussion of the latest developments and challenges serve this aim. Many recent state-of-the-art technologies are introduced in this book. Special emphasis is put on display quality, such as image sticking, contrast ratio and colour hue which have not been sufficiently dealt with in other books. Moreover, future trends and applications of liquid crystals materials and LC-devices following historical development and how they affect society are discussed. Of particular interest, emerging applications such as gas sensors and smart windows are covered.
Keywords: Liquid crystal displays.; Liquid crystals -- Computer simulation.; Liquid crystal displays -- Materials -- Computer simulation.; Solid-liquid equilibrium -- Mathematical models -- Computer simulation.; Liquid crystal devices.; elektronické knihy; electronic books